2003
DOI: 10.1177/009102600303200101
|View full text |Cite
|
Sign up to set email alerts
|

Career Mobility and Branding in the Civil Service: An Empirical Study

Abstract: This paper investigates recruitment and mobility patterns, and builds and tests a model that predicts voluntary turnover. The findings include why current employees joined, their motivations and problems in seeking posi tions once in the public service, and issues in transition management. The model found that promotion stress and commitment were primary causes for seeking new positions. However, this search favored remaining in the civil service. The model also suggested the importance of supervisory support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 21 publications
3
41
1
Order By: Relevance
“…Like previous studies (Shaw et al, 1998;Selden and Moynihan, 2000;Ito, 2003;Curry et al, 2005;Moynihan and Landuyt, 2008), we found mixed results concerning the effects of training on quit rates. The coefficient for the average amount spent on training per employee was not statistically significant (H7), which is consistent with Way's (2002) research.…”
Section: Resultssupporting
confidence: 62%
“…Like previous studies (Shaw et al, 1998;Selden and Moynihan, 2000;Ito, 2003;Curry et al, 2005;Moynihan and Landuyt, 2008), we found mixed results concerning the effects of training on quit rates. The coefficient for the average amount spent on training per employee was not statistically significant (H7), which is consistent with Way's (2002) research.…”
Section: Resultssupporting
confidence: 62%
“…That being said, studies of voluntary turnover have had mixed findings concerning the impact of training and development (Curry, McCarragher, & Dellmann-Jenkins, 2005;Haines, Jalette, & Larose, 2010;Ito, 2003;Moynihan & Landuyt, 2009;Selden & Moynihan, 2000;Shaw, Delery, Jenkins, & Gupta, 1998). However, strong training and development should lead to employees that feel valued by their organization and therefore demonstrate loyalty by choosing to stay with the organization.…”
Section: Training and Developmentmentioning
confidence: 99%
“…On one hand, such investment may signal that the organization values an employee, which in turn fosters a greater sense of employee loyalty to the organization (Curry et al, 2005). On the other hand, providing greater training to the employee may make them more skilled and capable of winning a job in other organizations (Ito, 2003). A research challenge that suggests itself is the need for a measurement strategy that can sort out the relative influence of these conflicting effects.…”
Section: Findings On Hrm Practicesmentioning
confidence: 99%